Expression of bcl-2 oncoprotein in pituitary tumours: comparison with c-myc. Issue 10 (October 1996) - Wang, D G; Johnston, C F; Atkinson, A B; Heaney, A P; Mirakhur, M; Buchanan, K D
Abstract : AIMS/BACKGROUND: Whereas the control of hormone secretion from pituitary adenomas has been studied in considerable detail, the molecular events underlying the development of these tumours are still poorly understood. Abnormalities of some oncogenes and tumour suppressor genes have been previously reported to occur at very low frequencies. The aim of the present study was to assess the possible expression of the bcl-2 oncoprotein and to compare it with that of c-myc in pituitary adenomas. METHODS: Monoclonal antibodies were used, along with microwave antigen retrieval and the avidin-biotin immunohistochemical method, to investigate expression of the oncoproteins bcl-2 and c-myc in 30 primary pituitary tumours from five broad diagnostic groups and in five normal pituitaries. RESULTS: Bcl-2 and c-myc immunoreactivities were detected in nine (30%) and eight (27%) tumour samples, respectively. Of the nine bcl-2 and eight c-myc positive tumours, seven were positive for both oncoproteins and included one of the four corticotrophinomas studied, four of seven prolactinomas, one of two somatotrophinomas, and one of four oncocytomas. All 13 null cell adenomas studied were negative for both bcl-2 and c-myc immunoreactivities. CONCLUSIONS: These results indicate that the bcl-2 and c-myc oncoproteins are expressed abnormally in over one quarter of pituitary tumours. Most these tumours co-expressed both oncoproteins. The genetic complementation of simultaneously deregulated bcl-2 and c-myc is implicated, through the regulation of apoptosis, in the pathogenesis of pituitary tumours.